A meta-analysis of global fungal distribution reveals climate-driven patterns - Větrovský, Tomáš; Kohout, Petr; Kopecký, Martin; Machac, Antonin; Man, Matěj; Bahnmann, Barbara Doreen; Brabcová, Vendula; Choi, Jinlyung; Meszárošová, Lenka; Human, Zander Rainier; Lepinay, Clémentine; Lladó, Salvador; et al. (Nature communications, 2019)
The evolutionary and environmental factors that shape fungal biogeography are incompletely understood. Here, we assemble a large dataset consisting of previously generated mycobiome data linked to specific geographical locations across the world. We use this dataset to describe the distribution of fungal taxa and to look for correlations with different environmental factors such as climate, soil and vegetation variables. Our meta-study identifies climate as an important driver of different aspects of fungal biogeography, including the global distribution of common fungi as well as the composition and diversity of fungal communities. In our analysis, fungal diversity is concentrated at high latitudes, in contrast with the opposite pattern previously shown for plants and other organisms. Mycorrhizal fungi appear to have narrower climatic tolerances than pathogenic fungi. We speculate that climate change could affect ecosystem functioning because of the narrow climatic tolerances of key fungal taxa.
Keywords: déšť; druhová specificita; Fungi; Temperature; biodiverzita; Internationality; Climate; Phylogeography; Species Specificity; internacionalita; houby; podnebí; teplota; fylogeografie; Biodiversity; Rain